Prudence Of Indonesia’s Identity in Digital Era: Students’ Awareness Towards Gender Discrimination - Mechelle Juana Chandra; Dea Fatmawati; Evita Fairuza Salsabila; Moh. Ayub Alchabib; Moses Glorino Rumambo Pandin (LPPM Institut Nasional Laa Roiba Bogor, 2022)
In this digital era, Indonesian people are required to have innovation and continue to make changes so that all wealth in Indonesia is not recognized by other countries. So, we need to build the value of tolerance considering that the social conditions of the multicultural Indonesian society have an impact where people often experience discriminatory actions, one of which is gender discrimination. Method: The methodology of this study is use of a qualitative survey and interview with students from any university in Indonesia. The population of this study is students from any university in Indonesia. The sample of this study is 45 students from 15-22 years old. Result: The results showed that on average, college students only knew enough about gender discrimination and most college students still found gender discrimination but had never experienced it. Recommendation: The authors suggests that further activities, students can continue to analyze and think of other effective actions to make people fully aware regarding gender discrimination in digital era. Limitation: The limitation of this study is this study has a limited time of research and difficult in conducting the research recall that we are on pandemic which makes the result of the research process is in delay. Keywords: gender discrimination, digital era, awareness